2018
DOI: 10.1186/s13104-018-3903-7
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D levels in a pediatric population of a primary care centre: a public health problem?

Abstract: ObjectiveVitamin D deficiency is a public health problem that occurs more frequently than expected. The aim of this study is to evaluate the vitamin D levels of children attending the paediatrics unit of the Bertamiráns primary care centre (A Coruña NW Spain). This is an observational study carried out during 1 year on a random sample of the pediatric population aged between 5 and 15 years. The levels of vitamin D (25(OH)D) were determined by immunoassay (ADVIA Centaur Vitamin D®). The results were classified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
(25 reference statements)
0
3
1
1
Order By: Relevance
“…The blood sample analysis shows the following prevalence: vitamin D sufficiency in 39.6% of the individuals, insufficiency 44.6% and deficiency 15.8%, respectively. These results might seem to show a high prevalence of hypovitaminosis for a healthy population, but are indeed relatively moderate in comparison to other studies published in different areas or latitudes of our planet ( be due to the fact that in this study their participants were exclusively of Caucasian origin, since, as is well known, the difference in skin pigmentation in different ethnic groups implies a higher risk of hypovitaminosis D [14, 17,18,28,32,[34][35][36][37].…”
Section: Discussioncontrasting
confidence: 57%
“…The blood sample analysis shows the following prevalence: vitamin D sufficiency in 39.6% of the individuals, insufficiency 44.6% and deficiency 15.8%, respectively. These results might seem to show a high prevalence of hypovitaminosis for a healthy population, but are indeed relatively moderate in comparison to other studies published in different areas or latitudes of our planet ( be due to the fact that in this study their participants were exclusively of Caucasian origin, since, as is well known, the difference in skin pigmentation in different ethnic groups implies a higher risk of hypovitaminosis D [14, 17,18,28,32,[34][35][36][37].…”
Section: Discussioncontrasting
confidence: 57%
“…20 A study done by Bustillo JM et al revealed that 66% of the children were found to have VDD. 21 A study by Shaka MF et al in apparently healthy children noted that 50.1% children had VDD. 22 All these studies show that VDD is quite high among pediatric population.…”
Section: Discussionmentioning
confidence: 99%
“…Protección de personas y animales: Los autores declaran que los procedimientos seguidos se conformaron de la bibliografía podemos inferir que existe una baja incidencia de insuficiencia de 25-OH-VD en nuestra muestra [4][5][6][7][8][9][10][11][12][13] . Por otro lado, el final del confinamiento coincidió con el final de la primavera; en los meses de verano los días tienen más horas de sol y una incidencia de rayos UVB más favorable para la síntesis de 25-OH-VD 18,19 , lo que provoca que se necesite menor exposición solar para un mismo nivel de 25-OH-VD 20 .…”
Section: Responsabilidades éTicasunclassified